Postcrisis Growth and Development : a Development Agenda for the G-20. - Fardoust, Shahrokh (World Bank Publications, 2010)
The Korea-World Bank High Level Conference on Post-Crisis Growth and Development, held in June 2010, in Busan, Republic of Korea, successfully brought key development issues to the forefront, laid the groundwork for setting global development priorities, and advanced the discussion among the international community, the G20, and the non-G20 countries on development policy. This volume compiles the papers and proceedings presented at this conference, which was attended by a mix of delegations from international organizations, high-level government officials, and eminent academics and practition.